PERAN LEMBAGA KEUANGAN SYARIAH DAN DAYA TARIK MASYARAKAT TERKHUSUS PADA SEKTOR UMKM - Aulia Daisy Arsy Syafitri; Devina Lutfa Dianti; Nadila Salsavira; Renny Oktafia (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
The Islamic Financial Sector (IFS) is a rapidly growing sector in the Islamic economy. IFS operates on Islamic law, so it must always adhere to Islam. IFS plays a crucial role in implementing Islamic principles aimed at helping society achieve prosperity, honesty, and fairness through a profit-sharing system. One of the key players in the Islamic financial sector is Islamic banking, which has a low credit risk, resulting in a sufficient margin for MSMEs. MSMEs, also known as Usaha Mikro Kecil dan Menengah (UMKM), are a type of productive business owned by individuals or corporations and regulated by Law No. 28 of 2008. UMKM has a significant role in Indonesia's economy. This potential is what motivates Islamic banks to facilitate the provision of loans to MSMEs. As time passes, Islamic banks have become capable of supporting MSMEs, which in turn attract MSMEs to conduct transactions at Islamic banks.